Odpowiedzi

  • Użytkownik Zadane
2013-07-13T13:30:30+02:00

7∛-4 = 2∛128x

7∛-4 = 2∛(2 * 64)x

7∛-4 = 2∛2 * ∛64 x

7∛-4 = 2∛2 * ∛4³x

7∛-4 = 2∛2 * 4x

7∛-4 = 8∛2 *x

x = (7∛-4) / (8∛2)

x = (7∛-2) / 8


2x + 3 = 6∛5 + x*∛320

2x + 3 = 6∛5 + x*∛(64 * 5)

2x + 3 = 6∛5 + x*∛64 * ∛5

2x + 3 = 6∛5 + x*∛4³ * ∛5

2x + 3 = 6∛5 + x*4 * ∛5

2x - 4x * ∛5 = 6∛5

x ( 2 - 4∛5) = 6∛5

x = 6∛5 / (2 - 4∛5)

 


2x+√2 = 1-√2x

2x + √2x = 1 - √2

x(2 + √2) = 1 - √2

x = (1 - √2) / (2 + √2)

x = [ (1 - √2)(2 - √2)] / [(2 + √2)(2 - √2)]

x = (2 - √2 - 2√2 + 2) / (4 - 2)

x = (4 - 3√2) / 2

x = 2 - 1,5√2